Chitinase production and antifungal potential of endophytic Streptomyces strain P4 - Tang-um,J. (Maejo University, 2015)
The endophytic actinomycete P4 strain, previously isolated from sweet pea root, was identified as Streptomyces sp. by full 16S rRNA sequencing. It is mostly related to Streptomyces griseoflavus with a 99.7% identity score. The Streptomyces sp. P4 was tested for its hydrolytic activities by plate method. The result showed the presence of chitinase. The extent of chitinase activity was assessed by spectrophotometric method along with growth monitoring. Chitinase production was growth-associated and showed the highest activity on the fifth day. The dual culture method revealed that the strain was effective in restricting the radial growth of Fusarium oxysporum f.sp. lycopersici, an important phytopathogen of tomato. Scanning electronic microscopic analysis showed that the rupture of the F. oxysporum mycelial cell wall occurred at the area of interaction between F. oxysporum and Streptomyces sp. P4. This was possibly due to the chitinolytic activity of the P4. Thus, this actinomycete has the potential for being used as a biocontrol agent, thereby reducing the use of chemical fungicides. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.